In vitro minimum growth for conservation of Drosophyllum lusitanicum - Gonçalves, Sandra (2013)
The present paper reports a protocol for minimum growth conservation of Drosophyllum lusitanicum (L.) Link. in vitro. Double-node cuttings were maintained for 4, 8 and 12 months at 5 or 25 ºC in the dark. The effects of sucrose either alone at 5, 20, 30, 40 and 60 g dm-3 or at 20, 40 and 60 g dm-3 in combination with 20 g dm-3 mannitol, on survival and post-storage shoot multiplication efficiency were investigated. The cultures could effectively be conserved under minimum growth at 5 ºC for 8 months on Murashige and Skoog’s medium supplemented with 60 g dm-3 sucrose, 20 g dm-3 mannitol and 0.91 μM zeatin. Following extended conservation, the cultures could be successfully regenerated into new shoots, and they were morphologically similar to those of non-stored controls.